2005
DOI: 10.1124/dmd.105.007369
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Substrate (Trifluoperazine) and Inhibitor (Amitriptyline, Androsterone, Canrenoic Acid, Hecogenin, Phenylbutazone, Quinidine, Quinine, and Sulfinpyrazone) “Probes” for Human Udp-Glucuronosyltransferases

Abstract: ABSTRACT:Relatively few selective substrate and inhibitor probes have been identified for human UDP-glucuronosyltransferases (UGTs). This work investigated the selectivity of trifluoperazine (TFP), as a substrate, and amitriptyline, androsterone, canrenoic acid, hecogenin, phenylbutazone, quinidine, quinine, and sulfinpyrazone, as inhibitors, for human UGTs. Selectivity was assessed using UGTs 1A1, 1A3, 1A4, 1A6, 1A7, 1A8, 1A9, 1A10, 2B7, and 2B15 expressed in HEK293 cells. TFP was confirmed as a highly select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
205
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(229 citation statements)
references
References 33 publications
24
205
0
Order By: Relevance
“…Inhibition studies on individual UGTs demonstrated that androsterone acted as a potent inhibitor of UGT2B7, while phenylbutazone acted as an inhibitor of UGT1A enzymes, which were in agreement with the previous study. 23 Androsterone (100 μM) exhibited potent inhibition against UGT2B7, whereas it showed none or muted inhibition against UGT1As. In the presence of androsterone (100 μM), the remaining activities of UGT2B7, UGT1A1, -1A3, and -1A8 were 12, 58, 84, and 58%, respectively.…”
Section: Chemical Research In Toxicologymentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition studies on individual UGTs demonstrated that androsterone acted as a potent inhibitor of UGT2B7, while phenylbutazone acted as an inhibitor of UGT1A enzymes, which were in agreement with the previous study. 23 Androsterone (100 μM) exhibited potent inhibition against UGT2B7, whereas it showed none or muted inhibition against UGT1As. In the presence of androsterone (100 μM), the remaining activities of UGT2B7, UGT1A1, -1A3, and -1A8 were 12, 58, 84, and 58%, respectively.…”
Section: Chemical Research In Toxicologymentioning
confidence: 99%
“…Androsterone and phenylbutazone have been reported as inhibitors of UGT2B7 and UGT1As, respectively. 23 They were employed in the chemical inhibition study to decipher the roles of individual UGTs in hepatic glucuronidation of DES. In view of the possibility of substrate-dependent inhibition occurring, their inhibitory effects on DES glucuronidation in individual UGTs were tested first in the present study.…”
Section: ■ Experimental Proceduresmentioning
confidence: 99%
“…[15][16][17] Glucuronidation is further influenced by induction, 18,19 phosphorylation, 20 the presence of genetic variants in the UGT coding regions leading to catalytically altered proteins, 21,22 by variants of the promoter regions leading to reduced UGT transcription, 4,13,23 as well as inhibitory effects of therapeutic drugs. Commonly administered drugs with inhibitory potential include amitriptyline, 24 protease inhibitors, 25 ketoconazole, 26 and acyl glucuronide adducts of ketoprofen. 27,28 Therefore, the combination of genetic variants in addition to environmental or therapeutic xenobiotic exposure defines glucuronidation activity and thus the potential risk profile of an individual.…”
mentioning
confidence: 99%
“…Inhibition of 1,25(OH) 2 D 3 monoglucuronide formation was evaluated using hecogenin, a known inhibitor of UGT1A4 [27,28]. Pooled HLM (0.5 mg/mL) or UGT1A4 Supersomes (1 mg/mL) were preincubated with alamethicin at 50 μg of alamethicin/mg of microsomal protein, and different concentrations (0, 5, 20, 50, 100, and 200 μM) of hecogenin for 10 min at room temperature, followed by the addition of 50 mM Tris-HCl (pH 7.4), 10 mM MgCl 2 , 5 mM saccharic acid 1,4-lactone, and 1 μM 1,25(OH) 2 D 3 .…”
Section: Inhibition Of 125(oh) 2 D 3 Monoglucuronide Formationmentioning
confidence: 99%
“…The assay was carried out as described above, except at a substrate concentration of 10 μM. N-glucuronidation rates for trifluoperazine, a known UGT1A4 specific substrate [24,25,26,27] were determined to compare 1,25(OH) 2 D 3 monoglucuronide formation rates with UGT1A4 activity using the same HLM (0.5 mg/mL). The trifluoperazine assay was carried out as described previously [26,28].…”
Section: Inter-liver Differences In 125(oh) 2 D 3 Monoglucuronide Fomentioning
confidence: 99%